Toward a Diagnostic Method of Organizational Health Based on Traditional Chinese Medicine - Tarride-Fernandez, M; Italo-Contreras, M (Emerald Publishing, 2023)
Purpose: The paper aims to propose a model and a comprehensive diagnostic method of organizational health status based on traditional Chinese medicine (TCM). Design/methodology/approach: The methodology is qualitative/interpretive and uses of the concept of functional homomorphism of WR Ashby is used, establishing similarities between the way in which this ancient medicine considers the human being and their condition as healthy to transfer it to an organization that produces goods and/or services. Findings: A healthy organization is conceived as one constituted by an association of people regulated by a set of norms based on certain purposes in a state of harmonious balance of their physical and energetic dimensions. In that the physical refers to storage functions, regulation and allocation of resources; transformation of raw materials and inputs into goods and services; waste disposal, distribution and coordination and with information systems for management control, while energy is associated with the ability to act with its management and policies. Research limitations/implications: The current paper is a first theoretical proposal, which should be enriched with practical applications that feedback its conceptual formulation, thus contributing to its validation. Practical implications: A comprehensive organizational diagnostic method is made available. Social implications: The proposed method allows a comprehensive organizational diagnosis, considering the participation of all the actors that make up this type of social systems. Originality/value: Although the methodological resource is old, the way it is used here is considered original, and it is also part of an original investigative process by the authors, oriented toward the search for comprehensive organizational diagnostic methods. © 2021, Emerald Publishing Limited.
Keywords: Healthy organizations; Organizational diagnosis; Traditional Chinese medicine